Research on User Integrated Positioning Management Platform - Baojun Liang (Dianxin kexue)
Based on the analysis of positioning technology and hybrid positioning capabilities platform, the implementation of user integrated positioning management platform was researched. It provided the positioning management information for customers and providers by positioning customer management, positioning authentication, business statistics of user positioning, analysis of positioning mode and success rate, positioning billing information. It is easy to promotion the applications of location-based business,enhance the upgrading of information technology application to the industry's development and customer value.